Effectiveness of instructional plan of child-rearing with emphasis on choice theory on improvement of parent-child relationship and life-satisfaction of mothers - zahra nili ahadabadi; fariborz bagheri; hossein salimi bajestani (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2019)
Infancy period is very important in life. This is a time of fundamental formation of character. In this investigation, effectiveness of instructional plan of child-rearing with emphasis on choice theory on improvement of parent-child relationship and life-satisfaction of mothers is studied. In this research, the assumption was that instruction of instructional plan of child-rearing with emphasis on choice theory is influential on parent-child relationship and life-satisfaction of mothers. This research was quasi-experimental with pre-post test and control group. The statistical population of this research consisted of all mothers living in Tehran. The sample consisted of 30 mothers. parent-child relationship Measure and Satisfaction with Life Scale are used in this study. Covariance test has been used for the analysis. The results showed that instructional plan of child-rearing has a meaningful influence on the parent-child relationship and life-satisfaction of mothers. Therefore this instructional plan can be effective on increase of parent-child relationship and life-satisfaction of mothers.